2013
DOI: 10.3109/13651501.2013.784791
|View full text |Cite
|
Sign up to set email alerts
|

Changes in health-related quality of life and functioning ability in help-seeking adolescents and adolescents at heightened risk of developing psychosis during family- and community-oriented intervention model

Abstract: Objective. Early intervention has been shown to benefit people at-risk for psychosis, but knowledge about how early intervention benefits all help-seeking adolescents is lacking. The aim of the present study was to study change in health-related quality of life (QoL) and functioning ability in help-seeking adolescents who participate in a community- and family-oriented early intervention program. Methods. The data was collected in Finland by an early-intervention team. Ninety help-seeking adolescents between 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…However, the decision on the duration and frequency can be an arbitrary one (some were as short but intensive as 3 days and other 3-5 years); it is dependent on the content of the intervention and change objectives. For example, in Granö et al (2013), within the JERI model (Table 1), the number of meetings and the length of the intervention is dependent on familial needs and ended when improvement is noticeable. Much of the decisions regarding formatting, setting, etc.…”
Section: Intervention Adoption and Implementation Flexibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, the decision on the duration and frequency can be an arbitrary one (some were as short but intensive as 3 days and other 3-5 years); it is dependent on the content of the intervention and change objectives. For example, in Granö et al (2013), within the JERI model (Table 1), the number of meetings and the length of the intervention is dependent on familial needs and ended when improvement is noticeable. Much of the decisions regarding formatting, setting, etc.…”
Section: Intervention Adoption and Implementation Flexibilitymentioning
confidence: 99%
“…In Belza et al (2006), the RE-AIM asks for whether or not outcomes were maintained over a year or two. Only five studies had evaluated their programme at 6 months or later: Turner et al (2007), Melo and Alarcão (2012), Granö et al (2013), Teder et al (2013), and Williamson et al (2014). Further, only two drew on RCT data in order to determine their interventions effectiveness (Bamberger et al, 2014;Turner et al, 2007;Zhong et al, 2011).…”
Section: Effectiveness and Maintenance Of Interventionsmentioning
confidence: 99%
“…HRQoL serves as a general mental health and well-being outcome measure in treatment studies among adolescents [13, 17, 18]. In a study by Granö et al [19], a need-adapted, family- and community-oriented intervention model improved HRQoL of help-seeking adolescents with mental health problems. A significant improvement in QoL was also seen in a study investigating the treatment outcome of inpatient psychotherapy among personality disordered adolescents [20] and in a study exploring adolescent mentalization-based integrative treatment among adolescents with anxiety, depression, or psychotic symptoms [21].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the family environment should be a specific target of treatment for individuals at risk for psychosis (Schlosser et al, 2010). Finally, previous studies have reported that adolescents with heightened risk of psychosis who seek help show significant improvement in psychotic experiences, quality of life, depression, anxiety, and hopelessness in a Family-and Community-orientated, need-adapted integrative treatment model (Granö et al, 2009(Granö et al, , 2013(Granö et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%